Effects of seed ingestion and herbivory by waterfowl on seedling establishment: a field experiment with wigeongrass Ruppia maritima in Doñana, south-west Spain - Figuerola, Jordi; Green, Andy J. (Kluwer Academic Publishers, 2004)
The ingestion of seeds by vertebrates usually affects the viability and/or germination rate of seeds. Increases in germination rate following passage through the vertebrate gut have often been assumed to be favourable for seedling survival and plant fitness, but this assumption has never been tested experimentally. Given that numbers of herbivorous waterfowl are higher in winter in Mediterranean wetlands, herbivory pressure there will be higher for early growing plants. In a factorial experiment we investigated the effects of seed ingestion by ducks (shov- eler, Anas clypeata) on the survival of wigeongrass Ruppia maritima seedlings in the field in Doñana (south-west Spain), under differing exposures to herbivory by waterfowl and fish. We planted ingested and non-ingested seeds in December, using exclosures to protect half of them from herbivores. When they were protected inside exclo- sures, there was no difference between ingested and non-ingested seeds in the number of plants that survived until June-July. However, fewer plants survived from ingested seeds when exposed to natural levels of herbivory because they were exposed for longer than plants germinating from non-ingested seeds. In conclusion, increases in germination rate after ingestion are not necessarily beneficial for the plant, and the final outcome depends on complex interactions with other factors such as herbivore abundance. Peer reviewed